2023
DOI: 10.3389/fendo.2023.1239398
|View full text |Cite
|
Sign up to set email alerts
|

The newly proposed alanine aminotransferase to high-density lipoprotein cholesterol ratio has shown effectiveness in identifying non-alcoholic fatty liver disease

Jiajun Qiu,
Maobin Kuang,
Ruijuan Yang
et al.

Abstract: ObjectiveAlanine aminotransferase (ALT) and high-density lipoprotein cholesterol (HDL-C) are important predictive factors for non-alcoholic fatty liver disease (NAFLD). The aim of this study was to analyze the association between the ALT/HDL-C ratio and NAFLD.MethodsWe conducted a retrospective analysis of data from 14,251 individuals participating in the NAGALA project’s health screening program. The presence of NAFLD was diagnosed based on the participants’ alcohol consumption status and liver ultrasonograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 61 publications
0
0
0
Order By: Relevance
“…У больных со стеатогепатитом выявлялся повышенный показатель FIB-4, который не исключал наличие фиброзных изменений в печени у данных больных. Полученные нами результаты согласуются с ранее полученными данными [26][27][28].…”
Section: Discussionunclassified
“…У больных со стеатогепатитом выявлялся повышенный показатель FIB-4, который не исключал наличие фиброзных изменений в печени у данных больных. Полученные нами результаты согласуются с ранее полученными данными [26][27][28].…”
Section: Discussionunclassified
“…Ruhl & Everhart (2010) noted that trunk fat plays a critical role in increasing ALT levels, suggesting that metabolically active intra-abdominal fat may contribute to liver injury. Additionally, Qiu et al (2023) The ratio of ALT to HDL-C was found to have a significant and positive relationship with the prevalence of non-alcoholic fatty liver disease (NAFLD). For every standard deviation increase in the ratio of ALT to HDL-C, the adjusted odds ratio (OR) for non-alcoholic fatty liver disease (NAFLD) among the participants increased by 3.05.…”
Section: Alanine Aminotransferasementioning
confidence: 99%